Possibilities of pharmacological thromboprophylaxis in microsurgery in real-world clinical practice - I. Yu. Zolotukhina; A. R. Kasimova; A. N. Potapov (Реальная клиническая практика: данные и доказательства)
Introduction. Thromboembolic complications represent several pathological processes and remain a common complication of most surgical interventions and one of the leading causes of failure in free flap transplantation. Thrombosis at the anastomotic site is not only the most common cause of failure in microsurgical operations, but it is also one of the factors leading to impaired circulation in free flaps and, as a consequence, the ineffectiveness of the performed treatment.Objective. The current review discusses the numerous ways of thromboprophylaxis that can play a role in ensuring flap survival after a well-performed surgery.Materials and methods. The initial search identified approximately 10,000 articles published from 1980 to September 2024. After reviewing the titles and abstracts, articles analyzing non-pharmacological methods of thromboprophylaxis, in which there are no indications of specific drugs, no indications of the outcomes of the experiment or clinical trial, as well as articles published in other languages or full-text versions of which are not published in the public domain were excluded. In total, 34 full-text articles were analyzed in the review.Results. This article considers drugs whose pharmacological action is aimed at preventing the formation of blood clots or their destruction (antiplatelet agents, anticoagulants, fibrinolytics) and drugs that indirectly, through other mechanisms of action, can reduce the likelihood of blood clots in transplanted flaps — dextran, prostacyclin, and nitric oxide. None of the analyzed studies indicated that the use of any group of drugs can lead to improved prognosis and reliably reduce the number of perioperative thrombotic complications.Conclusion. Higher-level studies are needed to examine the clinical use of antithrombotic drugs in microsurgery; however, given the low failure rate in current practice, a well-designed study, with all procedures performed by surgical teams with relevant experience and patients randomized to treatment groups, is needed to achieve adequate power.